Purification and Characterization of Acetylcholinesterase from Sheep Liver and Inhibition by Some Painkillers - Faruk Guloglu, Omer; Turkoglu, Vedat; Celik, Ismail (Asian Journal of Chemistry, 2010)
In this study, acetylcholinesterase (AChE; EC 3.1.1.7) was purified from sheep liver by affinity chromatography. The purification rate was found 3541.7 fold. The purification control of enzyme was done with sodium dodesilsulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The optimal pH, ionic strength and temperature of enzyme were determined. The optimal pH and the optimum temperature were 7.5–8.5 and 35ºC respectively. The highest activity was seen in concentration of 0.2 M (NH4)2SO4 as ionic strength. On the other hand, the inhibition effects of some painkiller, (paracetamol + caffein), (neostigmin methylsulfate) and (parace-tamol + propifenazon + caffein) were investigated in this study. According to results, the I50 values are 1.27 x 10–3, 1.02 x 10–4 and 1.236 M respectively. Also, Ki values are determined as 1.246 x 10–3, 4.326 x 10–5 and 1.646 x 10–3 mol–1 min–1 respectively.